Nitrogen-rich porous covalent imine network (CIN) material as an efficient catalytic support for C-C coupling reactions - Bhunia, Manas K.; Das, Swapan K.; Pachfule, Pradip; Banerjee, Rahul; Bhaumik, Asim (Dalton Transactions, 2012)
In an effort to expand the realm of possibilities of nitrogen-rich porous materials that could be used in catalysis, herein we report the synthesis of a new highly nitrogen rich (ca. 45%) porous covalent imine network (CIN-1) material employing simple Schiff base chemistry and further grafting its surface with palladium. Pd-loaded CIN-1 support acts as a truly heterogeneous catalyst towards Suzuki C-C coupling reaction between aryl halides with arylboronic acids. High surface area and excellent accessibility of the catalytic sites make it very efficient for heterogeneous catalysis. The stability of the catalyst due to intimate contact between nitrogen-rich organic support and metal allows several reuses with only a minor loss in catalytic activity.